APLIKASI FILOGENETIK DI DUNIA BIOLOGI KESEHATAN: MELACAK PANDEMI PATOGEN - Mahfut Mahfut (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
Phylogenetics is known as a study related to biological science. Phylogenetics provides facilities in the fields of human epidemiology, ecology, and evolutionary biology. In evolutionary science, this field of science is used to integrate spatial data in detecting the journey of living things over time. In health biology, the development of this science is also used to detect the spread of disease/pathogens from a region to the global direction. Phylogenetic analysis is able to describe the origin of the disease, the pattern of distribution, and speciation. In the pandemic analysis, several diseases that have been analyzed are the Chikungunya virus outbreak in 2007, Ebola and H3N2 influenza virus in 2014, and the SARS-CoV-2 virus in 2020. The study results reveal that the SARS-CoV-2 virus has three variants of lineage groups, namely types A, B, and C. The Covid-19 virus type A was first discovered in Wuhan City, China. Meanwhile, the type A virus mutation is seen in the United States and most of these viruses have also been found in corona positive patients from Australia. The Covid-19 type B virus was detected in patients living in East Asia, while the Covid-19 type was concentrated in the European region.